Development of Nursing Practice Guideline for The Prevention of Postpartum Hemorrhage after Cesarean Section in the Post-Anesthesia Care Unit Phrae Hospital - โปร่งใจ อุษา; แก้วอ้วน ยุพา (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2022)
The objectives were to 1) develop a nursing practice guideline to prevent hemorrhage in cesarean section patients and 2) study the outcomes of nursing practice guidelines for hemorrhage prevention for abdominal cesarean section patients in the Phrae Hospital recovery room. The participants were 19 registered nurses in the anesthetist unit. Data were collected between October 2018 to September 2019. The process consists of 8 steps: 1) Identify the issues to be developed and the development working group. 2) Establish objectives, target group, and result of the guidelines. 3) To find empirical evidence. 4) Assess the value of empirical evidence. 5) Determination as a guideline 6) Implementation the practice guidelines. 7) Reviewed the practice guidelines. 8) Evaluation and revision of empirical evidence implementation. The results showed that there were no patients with postoperative caesarean hemorrhage with shock, and no patients died from post-cesarean hemorrhage. All anesthetists’ nurses can follow nursing guidelines. The anesthetists’ nurses had the satisfaction to use the practice guideline at the high to the highest level. The practice guideline with the highest level of satisfaction was the practice guideline that improves patient safety by 68.40 %. The practice guidelines were able to provide care for the patient by 68.40%. The practices with a high level of satisfaction were the guidelines were easy to understand by 42.10% and convenient to use by 42.10%.